Penerapan Bimbingan Karir Ditinjau Dari Teori Trait And Factor Untuk Meningkatkan Keterampilan Pada Penyandang Disabilitas - Bagus Kurniawan Bagus; Suryati suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Application of Career Guidance in Review of Trait and Factor Theory to Improve Skills in Persons with Disabilities". This study aims first to find out how the skills of beneficiaries (PM) before being given career guidance in terms of trait and factor theory, secondly to find out how the application of career guidance is reviewed from trait and factor theory to improve skills in people with disabilities. This research uses qualitative research methods. with the Trait and Factor theory approach, the data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are data reduction, data display, conclusions / verification. as for the results of this study indicate that before implementing the application of career guidance in terms of trait and factot theory to improve skills in persons with disabilities at the budi perkasa Palembang center. It can be seen that the three research subjects have low self-understanding, which is indicated by their doubts about their abilities, interests, talents, and skills. They have not been able to optimize their potential skills due to uncertainty in understanding themselves.